Management of Suspected Acute Inflammatory Pancreatopathies in a “Real-World” Setting: A Single-Centre Observational Study - De Nuzzo, Daniele; Miconi, Alessia; Pierantognetti, Paola (JOP. Journal of the Pancreas, 2014)
Context Acute pancreatitis is defined as an acute inflammatory process in the pancreas with variable involvement of other regional tissues or remote organ systems. In Italy, the incidence ranges from 20 to 40 x100,000 inhabitants/year and the mortality rate ranges from 5 to 10%. Objective To assess the management of patients with suspected acute inflammatory pancreatopathy and to evaluate the impact of this management on clinical outcomes, including morbidity and mortality. Methods A “real-world” observational study based on the analysis of consecutive (one year) records from the Hospital Data Processing Centre: 112 cases with final diagnosis of "acute pancreatitis". Results and Conclusions Sixty-nine men and 43 women were analyzed; 91 (81.3%) patients were older than 40 years and 53 (47.3%) were older than 60 years. Two patients died. One-hundred and five patients (93.8%) had abdominal pain on admission. White blood cell count was greater than 15.0 x103/dL in 26 patients (23.2%). Hematocrit levels were greater than 40% in 30 patients (26.8%). Triglycerides were elevated in 21 patients (18.8%). In 3 of them (14.3%) levels were higher than 1,000 mg/dL. Creatinine was altered in 22 (19.6%) patients. CRP values were increased in all patients. In the majority of cases (58 patients; 51.8%) pancreatitis was of biliary origin, while alcohol accounted for 16 (14.3%) cases. Four tumors were found (3.6%). Forty patients (35.7%) were discharged in the first week, 41 (36.6%) in the second week, 19 (17.0%) in the third week, and 12 (10.7%) after 21 days. After 72 hours, acute pancreatitis was classified as mild in 80 patients (71.4%) and as severe in 32 patients (28.6%). Image: Pancreatopathies according to etiology and age (Figure 3)